2006
DOI: 10.1038/sj.npp.1301169
|View full text |Cite
|
Sign up to set email alerts
|

The Nociceptin/Orphanin FQ Receptor Agonist Ro 64-6198 Reduces Alcohol Self-Administration and Prevents Relapse-Like Alcohol Drinking

Abstract: Effects of the opioid receptor like-1 (ORL-1) receptor agonist Ro 64-6198 (0.1, 0.3, and 1.0 mg/kg intraperitoneally (i.p.)) on operant ethanol self-administration and activation of self-administration by ethanol deprivation were studied in male Wistar rats. Acute administration of Ro 64-6198 caused a dose-dependent reduction of ethanol self-administration. In comparison, the opioid antagonist naltrexone (0.1, 0.3, and 1.0 mg/kg i.p.) inhibited ethanol self-administration at all doses tested. Ethanol deprivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
77
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 45 publications
10
77
0
3
Order By: Relevance
“…Our findings are in agreement with previous studies showing that NOP receptors regulate the rewarding effects of various drugs of abuse (145,302,303). Specifically, previous studies have shown that activation of NOP receptors reduces anxiety (142), attenuates alcohol self-administration as well as cue-and stress-induced reinstatement of alcohol seeking (143). Cue-and stressinduced reinstatement to drug seeking are mediated by distinct brain pathways that ultimately converge, with cue-induced reinstatement primarily mediated by the mesolimbic DA system and stress-induced reinstatement primarily mediated by CRH and noradrenaline (304,305).…”
Section: Operant Self-administration Progressive Ratio Responding Ansupporting
confidence: 83%
See 4 more Smart Citations
“…Our findings are in agreement with previous studies showing that NOP receptors regulate the rewarding effects of various drugs of abuse (145,302,303). Specifically, previous studies have shown that activation of NOP receptors reduces anxiety (142), attenuates alcohol self-administration as well as cue-and stress-induced reinstatement of alcohol seeking (143). Cue-and stressinduced reinstatement to drug seeking are mediated by distinct brain pathways that ultimately converge, with cue-induced reinstatement primarily mediated by the mesolimbic DA system and stress-induced reinstatement primarily mediated by CRH and noradrenaline (304,305).…”
Section: Operant Self-administration Progressive Ratio Responding Ansupporting
confidence: 83%
“…These results are supported by previous findings where activation of NOP receptors decreases alcohol self-administration (141,143,298). The operant self-administration model better reflects motivation to obtain alcohol compared to home cage drinking which further strengthens these results.…”
Section: Operant Self-administration Progressive Ratio Responding Ansupporting
confidence: 82%
See 3 more Smart Citations